Study on Implicit-Type Fractional Coupled System with Integral Boundary Conditions - Longfei Lin; Yansheng Liu; Daliang Zhao (Mathematics, 2021)
This paper is concerned with a class of implicit-type coupled system with integral boundary conditions involving Caputo fractional derivatives. First, the existence result of solutions for the considered system is obtained by means of topological degree theory. Next, Ulam–Hyers stability and generalized Ulam–Hyers stability are studied under some suitable assumptions. Finally, one example is worked out to illustrate the main results.